VACCINE AGAINST PAPILLOMAVIRUS INFECTION AND CERVICAL CANCER - M.G. Galitskaya; L.S. Namazova (Педиатрическая фармакология, 2008)
Authors acquaint colleagues with the basic aspects of one of the most threatening disease of xxi century — cervical cancer, whose viral etiology is now beyond any doubt. They also showed an efficient method of prevention, which is vaccination against HPV, whose oncogenic strains are the main etiological factor of this disease.Key words: papillomavirus infection, cervical cancer, prevention, vaccination.